Pengaruh Love Of Money terhadap Kecurangan Pengelolaan Dana Desa - Melia Mardani; Herlina Helmy (Jurnal Eksplorasi Akuntansi, 2023)
This research tries to ascertain the impact of love of money on fraudulent village fund management. The Nagari in Tanah Datar Regency are the study's population., West Sumatra, amounting to 75 Nagari. The sample in this study was the Wali Nagari, secretary and treasurer in each nagari in Tanah Datar Regency. This study's research design, which employs primary data, is quantitative. Direct distribution of questionnaires to 225 respondents yielded the primary data. The data analysis technique in this study used a simple linear regression technique. The results of this study are Love of Money has a positive and significant effect on fraudulent village fund management in Nagari in Tanah Datar Regency.